2017
DOI: 10.1080/02646838.2017.1416336
|View full text |Cite
|
Sign up to set email alerts
|

Peer support workers’ experiences of supporting women with postnatal depression: a constant comparative exploration

Abstract: Findings indicate that PSWs choose to offer support based upon their own experiences, rejecting formal counselling therapies. This study found that peer-designed interventions do appear to have some merit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These findings are consistent with the mixed nature of research on peer support in the perinatal period. When well-trained, resourced and supervised, peer supporters can be an accessible and effective workforce [ 18 ], but fail to effectively support mothers without these forms of oversight in place [ 16 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the mixed nature of research on peer support in the perinatal period. When well-trained, resourced and supervised, peer supporters can be an accessible and effective workforce [ 18 ], but fail to effectively support mothers without these forms of oversight in place [ 16 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, however, the evidence-base on where peer supporters may most effectively fit within perinatal mental health service delivery remains unclear. Most of the research on peer support during the perinatal period has focussed on evaluating specific, formal interventions provided directly by peers, and the efficacy of these interventions has been mixed [ 16 20 ]. In contrast, there has been little research examining the other adjunctive or informal functions of peer support which are often widely available through charities, non-profit and non-governmental organisations, despite the fact that a recent review outside the perinatal period has found that these latter functions may offer greater clinical benefit [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a form of social support, it is often conceptualised as comprising emotional, appraisal (affirmational), and informational support (Dennis 2003). Different forms of organised peer support have previously been found to be effective in preventing and/or reducing PND among high-risk women and assisting recovery in women who have PND (McLeish and Redshaw, 2017a,b;Cust 2016a;Carter et al, 2018), for example, group peer support (Jones et al, 2014); telephone support (Dennis et al, 2009;Letourneau and Secco, 2015); and individual peer support (Cust, 2016a). This study uses a model of individualised peer support.…”
Section: The Proposed Interventionmentioning
confidence: 99%
“…Both groups of women also expressed a desire to regain control of their lives. Cultural differences and health care are influenced by the meaning that women are assigned according to their experiences and their behavior in seeking help (Carter, Cust, & Boath, 2018).…”
Section: Introductionmentioning
confidence: 99%